(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
This thesis examines how innovative technologies can enhance technology (handson vocational) lessons for students with hearing impairment. The aim is to justify an adapted instructional model based on visual-digital tools, simulations, and interactive step-by-step guidance to develop practical competencies. Methods include literature review, instructional design, classroom observation, and diagnostic assessment. Scientific novelty lies in proposing a multimodal visual instruction system with digital safety prompts and measurable performance criteria tailored to practice-oriented tasks